Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the quadratic equation [tex]\(3x^2 + 2x - 4 = 0\)[/tex], we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 3\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(c = -4\)[/tex].
Step 1: Calculate the discriminant
The discriminant [tex]\(\Delta\)[/tex] is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 2^2 - 4(3)(-4) \][/tex]
[tex]\[ \Delta = 4 + 48 \][/tex]
[tex]\[ \Delta = 52 \][/tex]
Step 2: Calculate the two solutions using the quadratic formula
The solutions are given by:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(\Delta\)[/tex]:
[tex]\[ x_1 = \frac{-2 + \sqrt{52}}{2 \cdot 3} \][/tex]
[tex]\[ x_2 = \frac{-2 - \sqrt{52}}{2 \cdot 3} \][/tex]
Step 3: Simplify and find the decimal values
First, we compute [tex]\(\sqrt{52}\)[/tex]:
[tex]\[ \sqrt{52} \approx 7.21 \][/tex]
Substitute this back into the equations for [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex]:
[tex]\[ x_1 = \frac{-2 + 7.21}{6} \][/tex]
[tex]\[ x_1 = \frac{5.21}{6} \][/tex]
[tex]\[ x_1 \approx 0.87 \][/tex]
For the second solution:
[tex]\[ x_2 = \frac{-2 - 7.21}{6} \][/tex]
[tex]\[ x_2 = \frac{-9.21}{6} \][/tex]
[tex]\[ x_2 \approx -1.54 \][/tex]
Therefore, the solutions to the quadratic equation [tex]\(3x^2 + 2x - 4 = 0\)[/tex] are:
[tex]\[ x_1 \approx 0.87 \][/tex]
[tex]\[ x_2 \approx -1.54 \][/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 3\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(c = -4\)[/tex].
Step 1: Calculate the discriminant
The discriminant [tex]\(\Delta\)[/tex] is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 2^2 - 4(3)(-4) \][/tex]
[tex]\[ \Delta = 4 + 48 \][/tex]
[tex]\[ \Delta = 52 \][/tex]
Step 2: Calculate the two solutions using the quadratic formula
The solutions are given by:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(\Delta\)[/tex]:
[tex]\[ x_1 = \frac{-2 + \sqrt{52}}{2 \cdot 3} \][/tex]
[tex]\[ x_2 = \frac{-2 - \sqrt{52}}{2 \cdot 3} \][/tex]
Step 3: Simplify and find the decimal values
First, we compute [tex]\(\sqrt{52}\)[/tex]:
[tex]\[ \sqrt{52} \approx 7.21 \][/tex]
Substitute this back into the equations for [tex]\(x_1\)[/tex] and [tex]\(x_2\)[/tex]:
[tex]\[ x_1 = \frac{-2 + 7.21}{6} \][/tex]
[tex]\[ x_1 = \frac{5.21}{6} \][/tex]
[tex]\[ x_1 \approx 0.87 \][/tex]
For the second solution:
[tex]\[ x_2 = \frac{-2 - 7.21}{6} \][/tex]
[tex]\[ x_2 = \frac{-9.21}{6} \][/tex]
[tex]\[ x_2 \approx -1.54 \][/tex]
Therefore, the solutions to the quadratic equation [tex]\(3x^2 + 2x - 4 = 0\)[/tex] are:
[tex]\[ x_1 \approx 0.87 \][/tex]
[tex]\[ x_2 \approx -1.54 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.